2020
DOI: 10.1038/s41598-020-65846-9
|View full text |Cite
|
Sign up to set email alerts
|

Internet use in old age predicts smaller cognitive decline only in men

Abstract: internet use provides cognitive stimulation and thereby may contribute to the accumulation of cognitive reserve that is proposed to be instrumental for maintaining cognitive health in ageing. As the first study so far, we examined possible gender differences in the relationship between Internet use and subsequent cognitive decline over six years assessed through changes in Trail Making Test (TMT) accomplishment time in 897 older adults. Latent change score modelling (taking into account baseline cognitive leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 78 publications
1
23
0
1
Order By: Relevance
“…Regarding gender differences in technology use, research shows that men are more likely to use and access various types of information and communication technology (ICT) than women are ( Kim et al, 2017 ). Research also shows that internet use in old age predicts a smaller cognitive decline only in men ( Ihle et al, 2020 ). Nevertheless, research on the gender differences in mHealth technology use among older adults with cognitive impairment is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender differences in technology use, research shows that men are more likely to use and access various types of information and communication technology (ICT) than women are ( Kim et al, 2017 ). Research also shows that internet use in old age predicts a smaller cognitive decline only in men ( Ihle et al, 2020 ). Nevertheless, research on the gender differences in mHealth technology use among older adults with cognitive impairment is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Using latent change score modeling, we modeled latent cognitive factors of TMT completion time in W1 (constructed from TMT parts A and B in W1) and W2 (constructed from TMT parts A and B in W2) as well as a latent cognitive change variable regarding change in TMT completion time from W1 to W2 [45, 46]. We included the following covariates to predict latent change: cognitive reserve, functional impairment in W1, the number of chronic diseases in W1, age in W1, sex, and the interaction of functional impairment in W1 with cognitive reserve (while taking the dependencies among all covariates into account).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Ihle et al [ 13 ] revealed in a six-year longitudinal study, the gender differences in the relationship between Internet use and cognitive decline, showing that more frequent Internet use predicted smaller subsequent cognitive decline only in men, but not in women. Together, these studies suggest the usefulness in incorporation of technology use in assessments for instrumental activities of daily living.…”
Section: Technology As An Aid In Diagnosismentioning
confidence: 99%